Peran Oleh Guru Dan Kepala Sekolah Dalam Mengimplementasikan Dengan Kurikulum Merdeka Belajar - Arni Yuniar Prastika; Muhitotun Nadhifah; Rafika Dini; Sofi Ullanuha Cahyani; Asih Andriyanti Mardliyah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In this study, the researchers focused on identifying the implementation in educational institutions carried out by teachers and principals that are included in the independent curriculum. In wri riting this article, the author uses a type of qualitative research using library research where the writer can examine from several sources, namely 6 national journals, which will be adjusted to the topic chosen by the author which will be used to strengthen the discussion of the reading in this article. which topics will use qualitative methods. The stages that the writer will carry out in collecting supporting materials are 1) collecting material containing problem topics, 2) analyzing each reading material which contains implementation in educational institutions carried out by teachers and school principals that are included in the independent curriculum. The results of the study in this article will explain the role played by teachers and principals in implementing schools in the self-learning curriculum. And in this article it aims to implement the efforts and methods of implementation in educational institutions carried out by teachers and principals which are included in the independent curriculum. In order for an agency in an educational institution to run well it will be in accordance with an independent curriculum.